Research handbook on entrepreneurship and innovation in family firms - Kraus, Sascha; Clauss, Thomas; Kallmuenzer, Andreas (Research handbooks in business and management series, 2023)
"This comprehensive Research Handbook offers new insights into how family businesses use entrepreneurship and innovation to address global challenges and ensure their survival and growth across generations. Using expertise from leading scholars around the world, this Handbook takes an international perspective and explores different national contexts and cultures. Key themes include theoretical advances and perspectives in entrepreneurship and innovation in family firms, current state-of-the-art research in entrepreneurship and innovation in family firms, and new and established research methods in entrepreneurship, innovation, and family firm research. Covering important concepts, including internationalization, governance, and resilience, this Research Handbook lays out a highly topical selection of advances in research on entrepreneurship and innovation in family firms. Examining the major overarching themes of theory, empirics and methods, this Research Handbook will be a valuable resource for scholars and advanced students of entrepreneurship, family business, organisational innovation, and organisation studies. It will also be useful for business leaders and practitioners in these areas"--